Teacher's pet - Hurwitz, Johanna; Hamanaka, Sheila (New York : Scholastic, 1989)
Nine-year-old Cricket's expectations of being, as always, the teacher's favorite student are dashed by the arrival of an unusual new girl in her fourth-grade class.
Booklist.
Bulletin (Center for Children's books).
4.7
3-6
Keywords: Friendship -- Fiction; Schools -- Fiction; Teachers -- Fiction; Friendship -- Fiction; School stories; Teachers -- Fiction